Genetic algorithm based approaches for the quadratic assignment problem - Yuan, Yu. (2009)
The quadratic assignment problem (QAP)belongs to the class of NP-hard combinatorial optimization problems. In this thesis, we describe several approaches based on genetic algorithms (GA)for the QAP.